Avalanche defences for the Trans-Canada Highway at Rogers Pass - Schaerer, P. A. (National Research Council of Canada, 1962)
In 1956 an Avalanche Observation Station was established at Glacier to obtain the information necessary for the specifications and design of the avalanche defence system for the proposed Trans-Canada Highway through Rogers Pass. This report contains a summary of the observations made and presents recommendations for the avalanche defence required. Preliminary studies indicated that a passive defence only would cause unacceptably long and frequent closures of the highway, but that the cost would be very high for a defence that would ensure an open highway. A defence system with three stages of construction combining active defence with passive defence by highway closures was recommended. With the completion of each stage the investment in defence structures and the costs for the avalanche control by explosives would be higher, but the length of time that the highway would probably have to be closed each winter would decrease. The first stage would be in operation when the highway was completed and the other two stages could be introduced later when more experience with the highway operation and avalanches was available. Peer reviewed: No NRC publication: Yes